Classroom Seating Management In Indonesian Middle School: English Teacher And Students’ Perspective - Sri Rejeki Amalia; Rahmadi Nirwanto; Hesty Widiastuty (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study aims to know the perspectives of the teacher and student in using classroom seating management in learning English at MTsN 2 Kota Palangka Raya. This study involved two classes that use different seating layouts, as follows pairs and table rows. Three students in each class would be picked up, so there would be 6 students, 2 homeroom teachers, and 2 English teachers to be interviewed. This study uses qualitative research with a case study method. A purposive sampling technique was used, where the research instruments included observation, interviews, and documentation studies are applied in this study. The result found that both of teacher's and students' perspectives show the same answer which agree the pair seating layout is more comfortable and effective to be used in the classroom in learning English than the table row seating layout. The students express that the pairs is fulfill their comfort during the teaching learning process in the classroom as the theory said. The teachers also confirm that the students is lack of active participation because of keep distracting by other students who start the chit-chat during the learning process on the table rows.